Association between alkaline phosphatase/albumin ratio and the prognosis in patients with chronic kidney disease stages 1–4: results from a C-STRIDE prospective cohort study - Xue, Xue; Li, Jia-Xuan; Wang, Jin-Wei; Lin, La-Mei; Cheng, Hong; Deng, Dan-Fang; Xu, Wen-Cheng; Zhao, Yu; Zou, Xin-Rong; Yuan, Jun; Zhang, Lu-Xia; Zhao, Ming-Hui; et al. (Frontiers in Medicine, 2023)
Background: Alkaline phosphatase-to-albumin ratio (APAR) has been demonstrated to be a promising noninvasive biomarker for predicting prognosis in certain diseases. However, the This is a provisional file, not the final typeset article relationship between APAR and prognosis in non-dialysis chronic kidney disease (CKD) patients remains unclear. This study aims to identify the association between APAR and prognosis among CKD stages 1-4 in China.Methods: Patients with CKD stages 1-4 were consecutively recruited from 39 clinical centers in China from 2011 to 2016. New occurrences of end-stage kidney disease (ESKD), major adverse cardiovascular and cerebrovascular events, and all-cause deaths were the outcome events of this study. Sub-distribution hazard competing risk and Cox proportional hazards regression models were adopted.Results: A total of 2180 participants with baseline APAR values were included in the analysis. In the primary adjusted analyses, higher APAR level (per 1-standard deviation [SD] increase in natural logarithm transformed[ln-transformed] APAR) was associated with 33.5% higher risk for all-cause deaths (adjusted hazard ratio [HR] 1.335, 95% confidence interval [CI] 1.068-1.670). Besides, there was evidence for effect modification of the association between APAR and ESKD by baseline estimated glomerular filtration rate (eGFR) (P interaction＜0.001). A higher APAR level (per 1-SD increase in ln-transformed APAR) was associated with a greater risk of ESKD among participants with eGFR ≥ 60 ml/min/1.73m 2 (adjusted SHR 1.880, 95%CI 1.260-2.810), but not in eGFR ＜ 60 ml/min/1.73m 2 .Conclusions: Higher APAR levels in patients with CKD stages 1-4 seemed to be associated with an increased risk of all-cause death. Thus, APAR appears to be used in risk assessment for all-cause death among stages 1-4 CKD patients.